Elevated Rates of Violence Victimization and Suicide Attempt Among Transgender and Gender Diverse Patients in an Urban, Safety Net Health System. Issue 2 (18th March 2021) - Progovac, Ana M.; Tran, Nathaniel M.; Mullin, Brian O.; De Mello Libardi Maia, Juliana; Creedon, Timothy B.; Dunham, Emilia; Reisner, Sari L.; McDowell, Alex; Bird, Natalie; Sánchez Román, María José; Dunn, Mason; Telingator, Cynthia; et al.
Abstract : The extent to which violent victimization may explain higher rates of suicidality for transgender and gender diverse (TGD) populations is not well‐understood. We identified likely‐TGD patients using 2008–2019 electronic health record data and compared them with non‐TGD patients to characterize differences in suicide attempt, ideation, and violent victimization. TGD patients ( n  = 916) had more suicide attempts (5.2 vs. 0.4 percent), ideation (20.5 vs. 1.8 percent), and violent victimization (5.4 vs. 1.7 percent, all p  < .001) than non‐TGDs ( n  = 511, 026). Violent victimization and TGD cohort were independent predictors of suicide attempt (odds ratios [ORs], 7.23 and 10.84) and ideation (ORs, 6.83 and 11.03, all p  < .001). We did not observe a differential impact of violent victimization for gender minorities. TGD patients are at higher baseline risk for suicidality, which is higher still for those experiencing violent victimization. Routine screening for both outcomes, including in primary care settings, may improve treatment.